Körper Beratung: Beratungshandeln im Spannungsfeld von Körper, Leib und Normativität - Wolf, Barbara; Wuttig, Bettina (transcript, 2019)
The transdisciplinary anthology presents different perspectives on counseling in the modes of bodily and normativity-critical analyses.